The Impact of Economic Indicators on Education Level of Women in Developing Countries - Kandemi̇r, Orhan (Kastamonu Egitim Dergisi, 2022)
Purpose: In the context of developing countries, it is to test the effect of economic factors such as per capita income, poverty level and income distribution unfairness on the education level of women. Methodology: In the study; cross-section analysis was performed by establishing a multiple regression model within the context of 82 developing countries included in the United Nations Development Program (UNDP) 2019 Human Development Report. While the dependent variable in the model is the proportion of women population aged 25 and over with at least secondary education (%), the independent variables are composed of economic variables such as the multidimensional poverty index, the inequality in income (%) and the gross national income per capita. The data are taken from UNDP's Human Development Report 2019. Findings: As expected as a result of the cross-section analysis, it was determined that as the income distribution unfairness and poverty increased, the proportion of women population aged 25 and over with at least secondary education (%) decreased, but as the level of gross national income per capita raised, the proportion of women population aged 25 and over with at least secondary education (%) also increased. Highlights: In developing countries, if the income distribution injustice and poverty are effectively tackled, gender inequality in education can be reduced more easily.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; Gender Equality; Education Level of Women; Income Distribution; Poverty; 5. Gender equality; 4. Education; 8. Economic growth; 1. No poverty; 10. No inequality